Supporting Japanese mothers of children with ADHD: cultural adaptation of the New Forest Parent Training Programme - Shimabukuro, Shizuku; Daley, David; Thompson, Margaret; Laver-Bradbury, Cathy; Nakanishi, Emi; Tripp, Gail (Wiley, 2017)
International practice guidelines recommend medication and behavioral intervention as evidenced-based treatments for attention deficit hyperactivity disorder (ADHD). Currently in Japan, the availability of non pharmacological interventions for ADHD is limited. We report the results of a pilot and a proof-of-concept study for a new behavioral intervention for Japanese mothers of children with ADHD. The pilot study delivered a standard six-session behavioral intervention and two parent-support sessions. Participants approved the group format and requested additional support to change parenting practices and behavioral strategies targeting ADHD symptoms. For the proof-of-concept study, the intervention was revised to include five sessions of pre intervention support followed by six sessions of the New Forest Parent Training Programme (NFPP), an evidence based intervention for ADHD. The revised intervention, NFPP-Japan, was associated with reductions in the mothers’ reports of children's ADHD symptoms and aggression, more effective parenting practices, and reduced parenting stress. The pilot and proof-of-concept studies indicate that it is possible to successfully modify Western behavioral interventions for Japanese mothers and to justify a randomized controlled trial evaluation of the NFPP-Japan, which is currently underway.